The development of Payroll System for Maju Iklasif Construction Sdn. Bhd / Masturina Mohamad - Mohamad, Masturina (2017)
Payroll System is a project that develops for Maju Iklasif Construction Sdn. Bhd. This system used by administrator in process calculates the salary of employee. Payroll System is computerized system that more systematic compared to manual system. The major problem faced by administrator when using manual system can cause miscalculation in calculate employee’s salary. Besides that, the administrator also has a problem in generate pay slips to employee. Since this company still used traditional method in manage their employee, developer take this opportunity proposed Payroll System to Maju Iklasif Construction Sdn. Bhd to minimize the problem faces by administrator. The objective of the development Payroll System is gathering and analyze requirement by user. Based on requirement gathering, developer will design the system. Then, Payroll System develops based on design. In order to achieve those objectives, developer used modified waterfall methodology that divide in five phase which are planning, requirement, analysis, design and implementation. There are some activity involve in each phase and also deliverable of document such as SRS and SDD. By developing Payroll System, the administrator can do their task easily and accurately. Besides that, this system make administrator performs task faster compared to current system that consume a lot of time. The outcome in develop Payroll System is bringing benefit to the company because have SMS and email notification to send information about employee’s salary and overtime claim. In future, there are some suggestions to enhance this system make it perform better which is this system also can use by employee and allow to manage their information by own.